2019
DOI: 10.1103/physrevb.99.115430
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal quantum gain facilitates loss compensation and plasmon amplification in graphene hyperbolic metamaterials

Abstract: Graphene-based hyperbolic metamaterials have been predicted to transport evanescent fields with extraordinarily large vacuum wave-vectors. It is particularly at much higher wave vector values that the commonly employed descriptional models involving structure homogenization and assumptions of an approximatively local graphene conductivity start breaking down. Here, we combine a nonlocal quantum conductivity model of graphene with an exact mathematical treatment of the periodic structure in order to develop a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In particular, it has been demonstrated that nonlocality in metamaterials may lead to enhancement of nonlinear response [ 11 ] or spontaneous emission [ 12 ]. Moreover, nonlocal response of hyperbolic metamaterials may result in new effects, such nonlocal quantum gain of plasmons [ 13 ], blueshift of intramolecular charge transfer emission [ 14 ], selective spatial filtering [ 15 ], or nonmagnetic optical isolation [ 16 , 17 ]. Furthermore, strong spatial dispersion enables us to obtain new degrees of freedom in controlling direction [ 18 ] and threshold of Cherenkov radiation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been demonstrated that nonlocality in metamaterials may lead to enhancement of nonlinear response [ 11 ] or spontaneous emission [ 12 ]. Moreover, nonlocal response of hyperbolic metamaterials may result in new effects, such nonlocal quantum gain of plasmons [ 13 ], blueshift of intramolecular charge transfer emission [ 14 ], selective spatial filtering [ 15 ], or nonmagnetic optical isolation [ 16 , 17 ]. Furthermore, strong spatial dispersion enables us to obtain new degrees of freedom in controlling direction [ 18 ] and threshold of Cherenkov radiation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an increasing number of studies has been devoted to new effects that arise in HMMs in the presence of spatial dispersion, including nonlocal quantum gain of plasmons [34], inverse transition radiation of controllable direction [35], large enhancement of decay rate of an emitter located inside a hyperbolic metamaterial [36], and blueshift of intramolecular charge transfer emission [37]. It has also been shown that with the help of nonlocality, it is possible to shape effective dispersion of HMMs [38] as well as to obtain highly selective spatial filtering [39] or nonmagnetic optical isolation [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial dispersion from the finite structural size is the underlying mechanism that prevents the elimination of the Cherenkov threshold from the elimination when the structural dimension is in the classical described regime. While in the quantum size regime, the dominance of the nonlocal electron screening in metals ensures that the threshold velocity is always larger than or equal to √ singularity or atomic-level thickness, such as the graphene-based metamaterials [114][115][116][117][118]. The platforms proposed here thus are fundamentally significant for exploring and regulating the interplays between the moving charged particle and artificial structures with a wide variety of geometries and materials.…”
Section: Discussionmentioning
confidence: 99%